a. (f –
g.(x) = –2x2 4x – 3
b. (f –
g.(x) = –2x2 – 2x 5
c. (f –
g.(x) = 2x2 2x 5
d. (f –
g.(x) = 2x2 – 2x 5
Answer:
Step-by-step explanation:
Given,
( Subtraction of two functions )
( By substituting values )
( Distributive property )
( Combining like terms )
Hence,
Option d is correct.
∠ XYT
∠ XTY
∠ TXY
Solution:
Given: △ RST ≅ △ TXY
We are given ΔRST and ΔTXY are congruent to each other.
If two triangles are congruent to each other then their corresponding parts are equal.
Please see the attachment of two triangles.
∵ ∠R=∠T By CPCT
∵ ∠XYT=∠STR By CPCT
∵ ∠XTY=∠SRT By CPCT
∵ ∠TXY=∠RST By CPCT
CPCT: Congruent part of congruence triangle.
Answer:
The answer should be B.) 2yw+y-1
Step-by-step explanation:
For this equation you:
Answer: The required solution is b = 0.
Step-by-step explanation: We are given to solve the following linear equation :
We need to find the value of the unknown variable 'b' in the give equation.
From equation (i), we have
Thus, the required solution is b = 0.